A curve passing through the point has the property that the perpendicular distance of the origin from the normal at any point of the curve is equal to the distance of from the -axis .
Let the equation of the curve be of the form
for integers and . where are coprime positive integers
Calculate .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us take the point P on the curve y = f ( x ) as P ( x 0 , f ( x 0 ) ) with its normal line expressible as:
y − f ( x 0 ) = ( f ′ ( x 0 ) − 1 ) ∗ ( x − x 0 ) ⇒ y = f ′ ( x 0 ) − 1 x + [ f ( x 0 ) + f ′ ( x 0 ) x 0 ] (i).
and the perpendicular distance line from the origin to (i) be:
y = f ′ ( x 0 ) x (ii).
Equating (i) with (ii) gives the intersection point Q:
Q ( x , y ) = ( f ′ ( x 0 ) 2 + 1 x 0 + f ( x 0 ) f ′ ( x 0 ) , f ′ ( x 0 ) 2 + 1 x 0 f ′ ( x 0 ) + f ( x 0 ) f ′ ( x 0 ) 2 ) (iii).
Now, the distance from Q to the origin equals the distance of P to the x-axis, or ∣ f ( x 0 ) ∣ . This can be expressed via the square of the 2-D distance formula:
f ( x 0 ) 2 = ( f ′ ( x 0 ) 2 + 1 x 0 + f ( x 0 ) f ′ ( x 0 ) ) 2 + ( f ′ ( x 0 ) 2 + 1 x 0 f ′ ( x 0 ) + f ( x 0 ) f ′ ( x 0 ) 2 ) 2 . (iv)
which after expanding and simplifying both sides of (iv) will give:
f ( x 0 ) 2 [ f ′ ( x 0 ) 2 + 1 ] = x 0 2 + 2 x 0 f ( x 0 ) f ′ ( x 0 ) + f ( x 0 ) 2 f ′ ( x 0 ) 2 ⇒ f ( x 0 ) 2 = x 0 2 + 2 x 0 f ( x 0 ) f ′ ( x 0 ) (v).
or 2 x y y 2 − x 2 = 2 x y − 2 y x = d x d y . Now make the substitution v = x y , d x d y = v + x d x d v to obtain:
v + x d x d v = 2 v − 2 v 1 ⇒ x d x d v = 2 v v 2 − 1 − 2 v 2 v 2 ⇒ x d x d v = − 2 v v 2 + 1 .
We can now obtain the separable first-order ODE − x d x = v 2 + 1 2 v d v , which integrates into − l n ( x ) + C = l n ( v 2 + 1 ) ⇒ − l n ( x ) + C = l n ( x 2 y 2 + 1 ) . Plugging in the boundary condition y = f ( 1 ) = 1 yields C = l n ( 2 ) , or:
l n ( x 2 ) = l n ( x 2 y 2 + 1 ) ⇒ x 2 = x 2 y 2 + x 2 ⇒ 0 = x 2 + y 2 − 2 x (vi)
with a = b = 1 , c = f = h = 0 , 2 g = − 2 . Hence the required coefficient sum is a + b + 2 g = 1 + 1 − 2 = 0 .